Ovarian maturation and haemolymphatic vitellogenic concentration of pacific white shrimp l. v (boone) fed increasing levels of total dietary lipids and hufa - Wouters (2001)
Ovarian maturation and haemolymphatic vitellogenic concentration of Pacific white shrimp L. V (Boone) fed increasing levels of total dietary lipids and HUFA